Transformational Leadership, Mindfulness, Readiness For Change And Lecturers’ Commitment To Teaching Entrepreneurship In Malaysian Polytechnics - Yeap, Sock Beei (2020)
Educators‘ entrance and retention in the teaching profession are related to their commitment to teaching. The study aimed to examine the influence of transformational leadership and mindfulness on lecturers‘ commitment to teaching entrepreneurship with the mediating effect of readiness for change in Malaysian polytechnics. The study employed explanatory sequential design, which the quantitative data would collect first and it followed by the collection of qualitative data to elaborate or explain the results of quantitative. Data were collected by using questionnaires and analysing by Statistical Package for Social Sciences (SPSS) and SmartPLS version 3.2.8 in the quantitative phase. Meanwhile, thematic analysis was performed by using Atlas.ti version 8.0 in the qualitative phase. Findings in quantitative phase showed that readiness for change mediated the relationship between transformational leadership and commitment to teaching entrepreneurship. However, findings did not support three hypotheses, which included (1) influence of transformational leadership on lecturers‘ commitment to teaching entrepreneurship, (2) influence of mindfulness on lecturers‘ commitment to teaching entrepreneurship; and (3) mediating role of readiness for change on the relationship between mindfulness and commitment to teaching entrepreneurship. In the second qualitative phase, themes of lecturers‘ professional commitment, commitment to teaching, professional preparation for teaching, and the significance of teaching entrepreneurship emerged to explain the quantitative results.